(untitled) (PERcursos Linguísticos, 2021)
The following work presents the English Language Pedagogical Residency Program as a subject of study. We aim to perform out a self-reflective analysis of the residency reports, highlighting the contributions of reflective writing developed during the program and the actions arising from it for teacher training. It is a qualitative documentary research, whose study is inserted in the field of Applied Linguistics. As a result, we conclude that reflective writing in the context of the English Language Pedagogical Residency, in fact has great relevance in teacher training. In short, from self-reflection I was able to increase my view about the importance of actions aimed at teacher training, as well as improving my skills as a future English language teacher. Key words: Pedagogical Residency. English Language. Self-reflexion.